PENGARUH TRIGLISERIDA TERHADAP KADAR LEPTIN PADA USIA LANJUT DENGAN GANGGUAN KOGNITIF - Yuliarni Syafrita; Lusi Eryanti (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2021)
There are some relationships between cognitive impairment with elevation of triglycerides and reduction of leptin concentration in elderly. The elevation of serum triglycerides concentration leads to leptin resistance resulting in impairment of leptin ability to cross blood brain barrier and decrease leptin concentration in brain. The aim of this study is to determine the correlation between triglycerides serum concentration towards leptin concentration in elderly with cognitive impairment. This was a cross sectional study conducted at Neurology Clinic Dr. M. Djamil Hospital. Cognitive function was assessed by using MoCA-Ina, concentration of triglycerides was measured by using enzymatic GPO-PAP method and concentration of leptin was measured by using ELISA. The correlation between two variables was analyzed by using Mann-Whitney test and correlation between triglycerides concentration with leptin was analyzed by using Spearman test. The p value ≤ 0.05 was statistically significant. There are mean triglycerides differences between elderly groups with cognitive impairment (160 (54 – 397)) and elderly groups with normal cognitive function (107 (53 – 249)) with p= 0.005. There are no leptin concentration differences between elderly with cognitive impairment (8,6 (0,96-36,92)) and elderly with normal cognitive function (11,73 (0,71 -36,66 )) with p= 0.45. There are negative correlations between triglycerides concentration with leptin concentration in groups with cognitive impairment, but the correlation is weak (r=0,347, p=0,134). There is negative correlation between triglycerides concentration with cognitive function. There is no correlation between leptin concentration in elderly with cognitive impairment.